2006
DOI: 10.1177/00222194060390020601
|View full text |Cite
|
Sign up to set email alerts
|

Arithmetic Processing in Children With Spina Bifida

Abstract: Three studies compared 98 children with spina bifida myelomeningocele (SBM)-a disorder associated with high rates of math disability and spatial deficits-to 94 typically developing children on multidigit subtraction and cognitive addition tasks. Children with SBM were classified into those with reading decoding and math disability, only math disability, and no reading or math disability. Study 1 showed that visual-spatial errors in multidigit arithmetic were not elevated in children with SBM. In Study 2, defic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
1
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 65 publications
(30 citation statements)
references
References 42 publications
2
25
1
1
Order By: Relevance
“…Individuals with Williams-Beuren syndrome have more severe, stable neurocognitive deficits that persist into young adult life (Howlin et al, 1998). Both children and adults with spina bifida meningomyelocele have difficulties in upper limb function (Dennis et al, 2009; Jewell et al, 2010) and mathematics (e.g., Barnes et al, 2006; Dennis and Barnes, 2002; Dennis, Berch, and Mazzocco, 2009). …”
Section: When To Assessmentioning
confidence: 99%
“…Individuals with Williams-Beuren syndrome have more severe, stable neurocognitive deficits that persist into young adult life (Howlin et al, 1998). Both children and adults with spina bifida meningomyelocele have difficulties in upper limb function (Dennis et al, 2009; Jewell et al, 2010) and mathematics (e.g., Barnes et al, 2006; Dennis and Barnes, 2002; Dennis, Berch, and Mazzocco, 2009). …”
Section: When To Assessmentioning
confidence: 99%
“…School-aged children with SB are more likely to experience problems with visual-motor and spatial skills, related difficulty in problem-solving and mathematical performance (Barnes, Pengelly, & Dennis, 2001), poor attention regulation, deficits in language, and less adaptive behavior. Specifically, regarding visual and spatial skills, a study by Snow (1999), found that children with SB exhibited severe deficits in visual planning and sequencing, compared not only with typically developing children, but also when compared to children with learning disabilities or Attention Deficit Hyperactivity Disorder (ADHD) or both.…”
Section: Cognitive Difficultiesmentioning
confidence: 99%
“…In contrast, children with severe TBI have worse performance than either children with mild injuries or community controls in several academic achievement domains during the early stages of recovery as well as 6 months to several years after the injury (Barnes et al, 2006; Barnes, Dennis, & Wilkinson, 1999; Ewing-Cobbs, Levin, et al, 1998; Jaffe et al, 1992, but see, Kinsella et al, 1995). It is not known whether injury severity affects math fact retrieval or aspects of math achievement other than calculations.…”
Section: Introductionmentioning
confidence: 95%
“…In some models, the ability to quickly and accurately retrieve answers to single-digit arithmetic problems (efficient math fact retrieval) is considered to be a foundational skill (Geary, Fan, & Bow-Thomas, 1992; Hecht, Torgesen, Wagner, & Rashotte, 2001) that is disrupted in individuals with mathematical disabilities with and without neurodevelopmental disorder (Barnes et al, 2006; Hanich, Jordan, Kaplan, & Dick, 2001). Children with math disability retrieve answers from memory less often than their typically developing peers, demonstrate more counting errors, use less developmentally mature strategies, and have highly variable math fact retrieval times (Geary, 1990; Hanich et al, 2001).…”
Section: Introductionmentioning
confidence: 99%